Development of an educational and monitoring mobile application for pregnant women in Nigeria - Babatunde, Abdulhammed Opeyemi; Ayede, Adejumoke Idowu; Colangelo, Amalia; Nguyen, Tuan Dung; Aborode, Abdullahi Tunde; Umeh, Charles; Hernandez, Maria Paula; Ayede, Oluwaseyi Iyanuoluwa; Ayede, Oluwatobiloba Oluwadunni (Frontiers in Public Health, 2025)
IntroductionNigeria accounts for 20% of all maternal mortality. Recently, more mobile health technology (mHealth) interventions are emerging in sub-Saharan Africa. The potential of mobile applications in maternal care has not been explored in Nigeria. This study describes the process of design, development, and testing of an educational and monitoring mobile application for pregnant women in Nigeria.MethodUsing a user-centered design, we conducted semi-structured interviews at each stage of mobile application development with pregnant women attending antenatal clinics in Oyo State, Nigeria. The first interview focused on empathy, followed by alpha and beta testing of the mobile application prototype at health facilities.ResultsThe barriers to accessing perinatal care were the distance to the nearest facility (mean = 3.3 km), lack of perinatal education, and cost. The low-fidelity prototype of the mobile application was designed with five features. Mobile applications increased the level of knowledge of preeclampsia by 179%. User feedback from alpha testing informed the development of a high-fidelity prototype for beta testing. Ninety-five percent (95%) of pregnant women surveyed were willing to download the mobile application. The final application developed was uploaded to the Google Play Store (MyBelle pregnancy application).ConclusionmHealth applications have the potential to increase access to prenatal information and services in Nigeria and may reduce maternal and childhood mortality. This study has described the process of development of the first indigenous mobile application specifically for pregnant women in Nigeria using a user-centered design thinking approach.